The Prevalence and Characteristic of Urinary Stone Disease in General Hospital of The Peripheral Area - Latuconsina, Yayan; Lantemona, Richard A; Mappiwali, Asrul; Pariputra, Yutha (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2024)
Introduction. Urinary stone disease (USD) refers to the formation of urinary calculi in the urinary system. The prevalence rates for urinary stones from 1% to 13% in different regions across the globe. The aim of this study is to determine the prevalence of USD patients who seek treatment at Tobelo Regional Hospital for the period of 2019-2023.Methods. A descriptive retrospective study based on medical records for the period of 2019-2023 conducted at Tobelo Regional General Hospital. The research subjects were all patients diagnosed with USD and had complete medical records.Results. A total of 320 individuals were studied. The prevalence rate of USD in our study population was commonly higher in men (56%) and in the age group of 40–59 years old (53%). Mostly found in private-employee groups (54%). Most were located in the kidney (83%). Stone diameter with a size > 1 cm was found in 103 cases (32%), and 33 of them were > 2 cm in size.Conclusions. USD cases are dominated by men rather than women, occurring mostly in the 40-59 years of age. Nephrolithiasis is the most common type of USD found in this study. Hospital facility improvements and high quality medical professionals may help the USD screening process to meet a prompt treatment.